Understanding Xenophobic Attacks in South Africa: A Systematic Literature Review - Bethuel Sibongiseni Ngcamu (Modern Africa)
South Africa is seen as an intolerant country when it comes to black immigrants of African origin. The existing literature agrees with this narrative on the hostility and resentment faced by immigrants, but there is limited empirical data on the effectiveness of government interventions. This study, therefore, systematically reviews the literature on the common themes that define xenophobia in South Africa. It examines the literature on the impact of xenophobic attacks on victims and the effectiveness of government response strategies. The study’s findings demonstrate that peer pressure, failure to provide the promised basic needs to the citizens, and denialism by the government all contribute to the xenophobic attacks in South Africa. The government’s ineffective interventions and scapegoating are seen as exacerbating the impact of attacks against immigrants.